Persepsi Mahasiswa IPII UIN Raden Intan Terhadap Pemanfaatan Software EPRINTS Universitas Negeri Yogyakarta Dalam Temu Kembali Informasi - Yunita, Irva; rahmat iqbal, `; Amaliah, Eni; Kesuma, Aghesna Rahmatika; Awaliyah, Anisatun; Rosnaida, Amelia (Universitas Islam Negeri Salatiga, 2024)
In the digital era, libraries are applying information technology to preserve, manage and provide access to digital collections. Software such as Eprints is the solution that libraries use to organize and manage these digital collections. It aims to help democratize access to scientific knowledge and facilitate the search and discovery of scientific research. The utilization of Eprints of Yogyakarta State University for IPII students of UIN Raden Intan Lampung aims to determine how satisfied the library users are with the ease of access, and the availability of the collection. The method used in the study was quantitative with a descriptive approach, researchers used data collection derived from questionnaires and observations distributed to IPII UIN Raden Intan Lampung students. This study consists of 3 indicators and 7 statements that researchers distributed to 23 IPII students. The first indicator of satisfaction with 2 statements with a mean value of 3.4 and 3.7 with a very high interval scale, the second indicator of satisfaction with 3 statements with an average value of 3.3, 3.3 and 3.4 with a very high interval scale and finally the third indicator regarding collections with an average value of 3.8 and 3.8 with a very high interval scale. With these results it can be said that IPII students as users feel very helpful in retrieving information with the use of Eprints UNY feel satisfied.